Interaction between irbesartan, peroxisome proliferator-activated receptor (PPAR-γ), and adiponectin in the regulation of blood pressure and renal function in spontaneously hypertensive rats - Afzal, S.; Sattar, M.A.; Johns, E.J.; Abdulla, M.H.; Akhtar, S.; Hashmi, F.; Abdullah, N.A. (Springer Verlag (Germany), 2016)
Adiponectin exerts vasodilatory effects. Irbesartan, an angiotensin receptor blocker, possesses partial peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist activity and increases circulating adiponectin. This study explored the effect of irbesartan alone and in combination with adiponectin on blood pressure, renal hemodynamic excretory function, and vasoactive responses to angiotensin II and adrenergic agonists in spontaneously hypertensive rat (SHR). Irbesartan was given orally (30 mg/kg/day) for 28 days and adiponectin intraperitoneally (2.5 μg/kg/day) for last 7 days. Groups of SHR received either irbesartan or adiponectin or in combination. A group of Wistar Kyoto rats (WKY) served as controls. Metabolic data and plasma samples were taken on days 0, 21, and 28. In acute studies, the renal vasoconstrictor actions of angiotensin II (ANGII), noradrenaline (NA), phenylephrine (PE), and methoxamine (ME) were determined. SHR control rats had a higher mean blood pressure than the WKY (132 ± 7 vs. 98 ± 2 mmHg), lower plasma and urinary adiponectin, creatinine clearance, urine flow rate and sodium excretion, and oxidative stress markers compared to WKY (all P < 0.05) which were progressively normalized by the individual drug treatments and to a greater extent by combined treatment. Responses to intrarenal administration of NA, PE, ME, and ANGII were larger in SHR (P < 0.05) than WKY by 20–25 %. Irbesartan enhanced (P < 0.05) responses to NA and PE, while adiponectin blunted responses to all vasoconstrictors (all P < 0.05). Combined treatment in SHR further decreased the renal vascular responses to ANGII. These findings suggest that an interactive relationship may exist between PPAR-γ, alpha adrenoceptors, and ANGII in the renal vasculature of the SHR.